Distribution of the residence time in a single-screw extruder with differing numbers of mixing elements - Seker, M (Blackwell Publishing Ltd, 2004)
Starch was extruded with sodium trimetaphosphate and sodium hydroxide in a single-screw extruder at 40% moisture content and screw speeds of 90 and 140 r.p.m. The effect of screw configurations, which included one and two mixing elements, on mean residence time, spread of residence time distribution (RTD), and flow pattern were determined. Increasing the screw speed and reducing the number of mixing elements reduced mean residence time. Higher RTD spread values were obtained at a screw speed of 90 r.p.m. when compared with 140 r.p.m. and increasing the number of mixing elements in the screw increased the RTD spread. The flow pattern was between plug and mixed flow, and increasing the number of a mixing element in the screw did not significantly affect the flow pattern in the single-screw extruder.
Keywords: extrusion; flow pattern; screw configuration; screw speed; starch